Educational Significance of Great Sculpture Works Established in the Years of Independence in the Republic of Uzbekistan - Madaminjon Ergashev (Genius Journals, 2022)
The works of sculpture created during the years of independence reflected new ideological and ideological, identity, national and historical themes. Large art monuments and statues have been erected in many cities of our country. Monumental sculptors have studied the glorious history of Uzbekistan, the rich heritage and cultural development of their ancestors, and managed to create a high artistic and glorious image of our ancestors. In this article we will talk about the educational significance of the majestic sculptures created during the years of independence of our country
Keywords: Sculpture; Primitive Society; Labor; Monumentalist,